The patent-competition interface in developing countries - Cheng, Thomas K. (Oxford : Oxford University Press, 2021)
This work proposes a development stage-specific approach to the patent-competition interface for developing countries, taking into account the different ways in which competition law regulation of patent exploitation practices interacts with various means of technology transfer.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on April 11, 2022).
Keywords: Patent laws and legislation -- Developing countries; Competition, Unfair -- Developing countries; Technology transfer -- Law and legislation -- Developing countries